Ankle stiffness assessment in individuals with chronic ankle instability in dual-task single leg stance on an unstable surface - Dias, Nuno (2022)
The shoulder of handball players suffers from the ongoing repetition of movement that may lead to the development of joint instability and modification of proprioceptive condition. Because the articular components of the shoulder joint are considered to have extreme importance on the static and dynamic stabilisation and quality of proprioceptive information, they may compromise the athlete’s performance. The purpose of our study was to verify if shoulder strength parameters (SSP) and joint position sense (JPS) of shoulder internal and external rotation may contribute to the development of shoulder instability in handball players.